VOICES IN MANY TONGUES: THE ROLE OF BILINGUALISM AND MULTILINGUALISM IN SHAPING IDENTITY AND CULTURAL INTEGRATION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This document explores the profound impact of bilingualism and multilingualism on individual identity, communication styles, and cultural integration within diverse sociololinguistic contexts. Drawing on theoretical frameworks from scholars such as Horner and Weber (2017), Bhatia (2017), Dewaele (2015), Aronin (2019), Hoffmann (2014), Angelelli (2015), Romaine (2017), Bernstein and Hamman-Ortiz (2019), and Schroedler (2021), this paper synthesizes various perspectives to illustrate how navigating multiple linguistic systems shapes self-perception, social interactions, and community cohesion. It examines phenomena like code-switching and language mixture, and highlights real-world examples from immigrant communities and multilingual societies like Canada and Barcelona. The paper concludes by emphasizing the critical role of linguistic diversity in fostering inclusive societies and the need for continued research in this evolving field.